The pheromone response factor coordinates filamentous growth and pathogenicity in Ustilago maydis. - Hartmann, H A (1996)
In Ustilago maydis, the a and b mating type loci regulate cell fusion, filamentous growth and pathogenicity. The a locus encodes a pheromone-based cell recognition system, and the b locus specifies two homeodomain proteins. The expression of all genes in the a and b loci is induced by pheromone. We have identified a HMG protein (Prf1) that binds sequence specifically to pheromone response elements present in the a and b loci. prf1 mutants do not express the a and b genes and are sterile. The disruption of prf1 in pathogenic haploid strains results in a loss of pathogenicity. The constitutive expression of the b genes restores pathogenicity and induces filamentous growth in the absence of the pheromone signal. These results provide evidence that pheromone signalling, filamentous growth and pathogenic development are linked through Prf1.